A ‘Despicable shambles’: labour, property and status in Faya-Largeau, Northern Chad - (:unkn) unknown (My University, 2016)
Faya-Largeau, the largest oasis in northern Chad, seems to present a classic picture of Saharan labour relations and status groups. Colonial officers spoke of nomadic ‘overlords’ who used to exploit sedentary ‘serfs’ of slave descent, but indirectly favoured the latter; today, former status relations are renegotiated, at times violently so. Access to vital resources, and especially agricultural land, is the focus of much contemporary conflict. Yet, on a closer look, this picture becomes less familiar: local agriculture requires little labour, property rights are uncertain, bilateral descent, exogamy and a high degree of mobility blur boundaries, while state involvement remains limited and ambiguous, and education little valued. Status, property and labour hence emerge as contextual categories that depend on as much as they constitute a historically specific and inherently unstable mode of production.
Keywords: African Research